Lorentz spaces of vector measures and real interpolation of operators. Issue 5 (3rd August 2020) - del Campo, R.; Fernández, A.; Mayoral, F.; Naranjo, F.; Sánchez Pérez, E.A.
Abstract: Using the representation of the real interpolation of spaces of p -integrable functions with respect to a vector measure, we show new factorization theorems for p -th power factorable operators acting in interpolation couples of Banach function spaces. The recently introduced Lorentz spaces of the semivariation of vector measures play a central role in the resulting factorization theorems. We apply our results to analyze extension of operators from classical weighted Lebesgue L p -spaces — in general with diﬀerent weights — that can be extended to their q -th powers. This is the case, for example, of the convolution operators defined by L p -improving measures acting in Lebesgue L p -spaces or Lorentz spaces. A new representation theorem for Banach lattices with a special lattice geometric property, as a space of vector measure integrable functions, is also proved.